THE POLITICAL ECONOMY OF CHINA-MYANMAR BILATERAL RELATIONS UNDER THE FRAMEWORK OF BELT AND ROAD INITIATIVE - Aung, Kyaw Htet (Universitas Muhammadiyah Yogyakarta, 2020)
After the political transition of Myanmar in 2011, China?s engagement strategy toward Myanmar has led the changes from the state-to-state relations into the multi-layered relations. At the same time, Myanmar?s foreign policy has also challenged Beijing?s economic and political interests in Myanmar in terms of the Myit-Sone Dam suspension by Myanmar?s first reform government. Later, the Aung San Suu Kyi?s government looks more closely with the PRC under the framework of the Belt and Road Initiative. In this sense, it could be interesting to find Myanmar?s policy on China?s engagement and China?s responses to Myanmar?s development. Moreover, Myanmar has agreed to the China-Myanmar Economic Corridor (CMEC) which is a strategically important economic corridor under the umbrella of China?s Belt and Road Initiative (BRI). Among various China?s BRI projects in Myanmar, every case has a different characteristic, pattern, and situation, in terms of the different fundamental interaction relations among the state, market, and society. It means that China?s interest in Myanmar is a complicated and complex situation during Myanmar?s new political order. In this sense, the China-Myanmar bilateral relations have the multidimensional factors and it was shaped by the diverse state-holders? interaction. Therefore, this paper will seek the China-Myanmar bilateral relations from the political economy perspective. At last, this paper will argue that the changing relations among state-market-society in Myanmar will play a crucial role in China-Myanmar bilateral relations by using the two-level game theory.